2001
DOI: 10.1002/jrs.746
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced resonance Raman spectroscopy of water‐insoluble Ni(II) porphine adsorbed on aqueous silver sol: suppression of antisymmetric scattering, antiresonance effect and higher order scattering

Abstract: With the intention of examining how adsorption on a SERS-active surface affects the electronic resonance enhancement in surface-enhanced resonance Raman scattering (SERRS) from Ni(II) porphine (NiP), we acquired high-quality SERR spectra from very low concentrations of NiP (∼10 −8 M) in aqueous Ag sol from 50 to 3500 cm −1 with excitations across both the Soret and Q absorption bands. Water-insoluble NiP was transferred to aqueous silver sol surface by using pyridine as carrying solvent, taking advantage of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…This indicates an edge-on adsorption geometry for reasons detailed above but is in direct contrast with the observations of Li et al who observed a selective enhancement of the b 2g modes for NiP. 30 Thus, while it is entirely likely that NiP is adsorbed through the CC bond, the ethyl groups attached to each b-carbon in NiOEP present a substantial steric hindrance to this adsorption geometry. Thus, from the preferential enhancement of b 1g modes, it is tentatively suggested that NiOEP is adsorbed edge-on with the C 2 00 -axis normal to the electrode surface.…”
Section: Rr Spectracontrasting
confidence: 62%
See 3 more Smart Citations
“…This indicates an edge-on adsorption geometry for reasons detailed above but is in direct contrast with the observations of Li et al who observed a selective enhancement of the b 2g modes for NiP. 30 Thus, while it is entirely likely that NiP is adsorbed through the CC bond, the ethyl groups attached to each b-carbon in NiOEP present a substantial steric hindrance to this adsorption geometry. Thus, from the preferential enhancement of b 1g modes, it is tentatively suggested that NiOEP is adsorbed edge-on with the C 2 00 -axis normal to the electrode surface.…”
Section: Rr Spectracontrasting
confidence: 62%
“…The lack of significant changes in the relative intensities of the totally symmetric modes under Soret-resonance has been observed by Li et al in the SERRS spectra of nickel porphine, NiP. 30 The authors attributed the invariance of the relative intensities of the a 1g modes as indicative of a dominant Franck-Condon RR enhancement mechanism operating in conjunction with an increased scattering efficiency resultant from surface adsorption. Li et al noticed that b 1g modes were much weaker than b 2g modes in the SERRS spectra, whereas in the RR spectra, the enhancement pattern was reversed.…”
Section: Rr Spectramentioning
confidence: 80%
See 2 more Smart Citations
“…The observation of overtones and combinations of fundamental vibrations that appear above 1000 cm À1 in SERS/ SERRS experiments is very scarce. [24][25][26][27] The first experimental evidence for such overtones in SERS experiments was reported by Pettinger in the study of pyridine adsorbed on silver electrodes. 24 The next report on the observation of overtones in SERS/SERRS experiments appeared only 10 years later by Aroca and Clavijo 25 investigating the SERRS spectra of a perylene dye on a Langmuir-Blodgett layer on Ag island films.…”
Section: Introductionmentioning
confidence: 96%